2018
DOI: 10.1002/ange.201808551
|View full text |Cite|
|
Sign up to set email alerts
|

Digging the Sigma‐Hole of Organoantimony Lewis Acids by Oxidation

Abstract: The development of group 15 Lewis acids is an area of active investigation that has led to numerous advances in anion sensing and catalysis. While phosphorus has drawn considerable attention, emerging research shows that organoantimony(III) reagents may also act as potent Lewis acids. Comparison of the properties of SbPh3, Sb(C6F5)3, and SbArF3 with those of their tetrachlorocatecholate analogues SbPh3Cat, Sb(C6F5)3Cat, and SbArF3Cat (Cat=o‐O2C6Cl4, ArF=3,5‐(CF3)2C6H3) demonstrates that the Lewis acidity of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…52 Very recently, Yang et al have shown how to "dig" a deeper σ-hole by oxidizing antimony(III) to the +V state. 53 Historical work has been reported on the interaction of SbF 3 with Lewis bases; however, the resulting compounds have very rarely been examined in the context of noncovalent PnB. A recent review by Scilabra et al inventories the relevant published structures and discusses them anew in this context.…”
Section: Introductionmentioning
confidence: 99%
“…52 Very recently, Yang et al have shown how to "dig" a deeper σ-hole by oxidizing antimony(III) to the +V state. 53 Historical work has been reported on the interaction of SbF 3 with Lewis bases; however, the resulting compounds have very rarely been examined in the context of noncovalent PnB. A recent review by Scilabra et al inventories the relevant published structures and discusses them anew in this context.…”
Section: Introductionmentioning
confidence: 99%
“…17 The high Lewis acidity of [3] 2+ also comes to light using Ph 3 PO as a probe. 18 Indeed, 31 P NMR measurements in CH 2 Cl 2 show a larger deshielding of the phosphorus resonance upon addition of [3][BArF 24 ] 2 to Ph 3 PO (Δδ = 7.9 ppm for a 6 mM 1:1 mixture) than with [2][BArF 24 ] (Δδ = 6.1 ppm for a 6 mM 1:1 mixture).…”
mentioning
confidence: 99%
“…The expected mechanistic pathway for the synthesis of bis-4-hydroxycoumarins is shown in Scheme 2. SbPh 3 has no such significant strong Lewis acid activity, 22 but the catalyst is so effective that a very small amount (0.02 g) of SbPh 3 is adequate for successful completion of the reaction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%